PENGARUH BIMBINGAN BELAJAR TERHADAP HASILBELAJAR MAHASISWA PADA MATAKULIAH KALKULUS DIFERENSIAL - Abdul Azis; Usman Usman; khairul Umam (Jurnal Peluang, 2020)
This study aims to investigate the effect of tutoring on student learning outcomes. This study employed a descriptive and quantitative approach. The population of this research was the first year students of the Mathematics Education Study Program for the 2019/2020 academic year. The research sample was 50 students, selected by purposive sampling from four classes of students. Data collection was conducted using the test instrument for student learning outcomes before and after the tutoring. The data were analyzed using the t-test. The results showed that there was a significant effect of tutoring on student learning outcomes in the differential calculus course. Tutoring activities outside of lecture activities need to be continued in other courses in future lectures.